Answer:
The difference is: [tex]4[/tex]
Step-by-step explanation:
In order to solve this exercise it is important to remember that:
1. The result of a Subtraction is known as "Difference".
2. The multiplication of signs:
[tex](+)(+)=+\\(-)(-)=+\\(-)(+)=-\\(+)(-)=-[/tex]
According to the information given in the exercise you know that the following expression represents Lindsey's score on the first round of a golf tournament:
[tex]a+3[/tex]
And the expression that represents Lindsey's score on the second round of that golf tournament is:
[tex]a-1[/tex]
Therefore, you can find the difference between Lindsey's scores in those rounds by subtracting those two expressions.
Then, you get that this is:
[tex](a+3)-(a-1)=a+3-a+1=4[/tex]